2012
DOI: 10.1111/j.1540-8159.2012.03516.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Bridging Around Device Surgery: Compliance with Guidelines

Abstract: Our study identified significant underutilization of bridging, particularly in the postoperative period, in patients at "moderate/high risk" of thromboembolism. Conversely, bridging was overused in "low risk" patients and associated with bleeding complications. Physicians should be urged to follow current expert guidelines in regard to bridging anticoagulation for cardiac rhythm device surgery. (PACE 2012;35:1480-1486).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…Uninterrupted warfarin therapy seems be safer than bridging therapy in terms of bleeding complications and perhaps in preventing thromboembolic complications though the latter remains to be further defined. Uninterrupted warfarin therapy would provide a more uniform approach to anticoagulation therapy in the perioperative period than the present marked variability in the application of the current guidelines with and without recommendations for bridging . Uninterrupted warfarin therapy with a therapeutic INR in patients with moderate to high thromboembolic risk avoids heparin therapy and it appears safe, simple, and cost‐effective.…”
Section: Should the Current Guidelines Be Changed?mentioning
confidence: 99%
See 3 more Smart Citations
“…Uninterrupted warfarin therapy seems be safer than bridging therapy in terms of bleeding complications and perhaps in preventing thromboembolic complications though the latter remains to be further defined. Uninterrupted warfarin therapy would provide a more uniform approach to anticoagulation therapy in the perioperative period than the present marked variability in the application of the current guidelines with and without recommendations for bridging . Uninterrupted warfarin therapy with a therapeutic INR in patients with moderate to high thromboembolic risk avoids heparin therapy and it appears safe, simple, and cost‐effective.…”
Section: Should the Current Guidelines Be Changed?mentioning
confidence: 99%
“…Uninterrupted warfarin therapy with a therapeutic INR in patients with moderate to high thromboembolic risk avoids heparin therapy and it appears safe, simple, and cost‐effective. On this basis we suggest that the guidelines be modified with a statement to reflect the two strategies (bridging vs uninterrupted warfarin) are equally applicable for implantation of cardiac rhythm devices at this time without waiting for the results of several randomized trials that will address the remaining uncertainty of periprocedural bridging anticoagulation . With uninterrupted warfarin therapy, on the day of surgery the INR should be <3.0 and ideally between 2 and 2.5.…”
Section: Should the Current Guidelines Be Changed?mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, different studies have shown that implantation of CRMDs under active OAC in high TE risk patients is not only safe, but also associated with a lower incidence of pocket bleeding complications when compared with the classic heparin bridging strategy . In any case, both strategies rely on an adequate classification of patients according to their TE risk and this process may be time consuming and subjected to a great variability depending on the attending physician criteria …”
Section: Introductionmentioning
confidence: 99%